Managing learning communities to improve student learning outcomes: A systematic literature review - Saguh Miliarto; Nurul Falah Rahmawati (Inovasi Kurikulum, 2025)
This study aims to analyze the management of learning communities as a strategy to improve student learning outcomes through a Systematic Literature Review (SLR). The review covered academic literature published between 2018 and 2024, indexed in the Directory of Open Access Journals (DOAJ). A total of 10 eligible articles were selected and analyzed using qualitative content analysis, which consisted of four stages: open coding, axial coding, selective coding, and theoretical coding. The findings led to an integrative model of learning community management, encompassing four fundamental dimensions: structural, functional, contextual, and impact on learning outcomes. The structural dimension highlights the importance of competence stratification, role rotation, and multi-stakeholder coordination. The functional dimension involves knowledge sharing, systematic reflection, and the transformation of pedagogical practices. The contextual dimension emphasizes adaptability to socio-cultural conditions, the use of technology, and the accommodation of diverse learning needs. Meanwhile, the impact dimension includes improvements in cognitive competence, strengthening of non-cognitive aspects, institutional capacity, and school identity. The study also identifies moderating variables, including transformative leadership, institutional policy support, and integrated learning infrastructure.   Abstrak Penelitian ini bertujuan untuk menganalisis pengelolaan komunitas belajar sebagai strategi peningkatan capaian belajar murid melalui pendekatan Systematic Literature Review (SLR). Kajian dilakukan terhadap literatur akademik yang dipublikasikan pada periode 2018–2024 dan terindeks dalam Directory of Open Access Journals (DOAJ). Proses seleksi menghasilkan 10 artikel yang memenuhi kriteria inklusi, dianalisis menggunakan teknik analisis konten kualitatif dengan empat tahapan: open coding, axial coding, selective coding, dan theoretical coding. Hasil analisis menunjukkan terbentuknya model integratif pengelolaan komunitas belajar yang mencakup empat dimensi fundamental, yakni struktural, fungsional, kontekstual, dan dampak terhadap capaian belajar. Dimensi struktural menekankan pentingnya stratifikasi kompetensi anggota, rotasi peran, dan koordinasi multistakeholder. Dimensi fungsional mencakup berbagi pengetahuan, refleksi sistematis, dan transformasi praktik pedagogis. Dimensi kontekstual menegaskan adaptabilitas terhadap kondisi sosio-kultural, pemanfaatan teknologi, dan keragaman kebutuhan pembelajaran. Sementara itu, dimensi dampak mencakup peningkatan kompetensi kognitif, penguatan aspek non-kognitif, kapasitas institusional, serta identitas sekolah. Penelitian ini juga mengidentifikasi variabel moderator berupa kepemimpinan transformatif, dukungan kebijakan institusional, dan infrastruktur pembelajaran terintegrasi. Kata Kunci: capaian belajar; komunitas belajar; pendidikan kolaboratif; pengelolaan pendidikan